Case Report: Resection of Giant Endotracheal Hamartoma by Electrosurgical Snaring via Fiberoptic Bronchoscopy in a 9-Year-Old Boy - Wu, Lei; Chen, Wei; Li, PengCheng; Li, Shuxian; Chen, Zhimin (Frontiers in Pediatrics, 2021)
Endotracheal hamartomas are rarely encountered in children. Symptoms caused by the tumors may include cough, dyspnea, hemoptysis, chest pain, purulent sputum, and fever. The nonspecific symptoms result in a delayed diagnosis. Among the various treatment of this rare disease, surgical resection seems to be the most popular treatment. Endoscopic treatment is rarely described. In this report, we describe a 9-year-old boy with an endotracheal hamartoma which was successfully excised by electrosurgical snaring via fiberoptic bronchoscopy. Our case demonstrates that it is feasible to remove an endotracheal hamartoma with snare probe of electrocautery systems. The resection of selected benign endotracheal tumors in children can be conducted using electrocautery which can be regarded as an alternative therapy.